2016
DOI: 10.1038/srep23119
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Structural Phase Transition in VO2 by Epitaxial Strain in Vicinity of Metal-insulator Transition

Abstract: Mechanism of metal-insulator transition (MIT) in strained VO2 thin films is very complicated and incompletely understood despite three scenarios with potential explanations including electronic correlation (Mott mechanism), structural transformation (Peierls theory) and collaborative Mott-Peierls transition. Herein, we have decoupled coactions of structural and electronic phase transitions across the MIT by implementing epitaxial strain on 13-nm-thick (001)-VO2 films in comparison to thicker films. The structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
71
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(76 citation statements)
references
References 60 publications
4
71
1
Order By: Relevance
“…Another important alternative is strain-engineering, which has long been used as an effective and predictable means for tuning the materials properties [11][12][13][14][15][16], including strain-induced structural phase transitions [17][18][19], indirect-direct band gap transition [11][12][13], and semiconductormetal transition [12,20]. Previous work [4,21,22] also demonstrated the possibility of applying strains to tune the thermoelectric power factor.…”
Section: Introductionmentioning
confidence: 99%
“…Another important alternative is strain-engineering, which has long been used as an effective and predictable means for tuning the materials properties [11][12][13][14][15][16], including strain-induced structural phase transitions [17][18][19], indirect-direct band gap transition [11][12][13], and semiconductormetal transition [12,20]. Previous work [4,21,22] also demonstrated the possibility of applying strains to tune the thermoelectric power factor.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the scenario can be even more complex if we consider films of VO 2 . As pointed out by Fan et al [8], investigating thin and ultrathin VO 2 films grown on oriented TiO 2 substrates, the strain dynamics also play a role and, in these films, the MIT process is modulated continuously via the interfacial strain [9,12,13]. The presence and role of different phases and the relationship between the phase transition temperature and strain have been investigated during film growth.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the interfacial strain strongly affects the electronic orbital occupancy, which changes also the electron-electron correlation and controls the phase transition temperature. Recently Mengmeng Yang et al [9] investigated the MIT mechanism in a 13 nm thick strained VO 2 film on TiO 2 . With temperature-dependent synchrotron radiation high-resolution X-ray diffraction data and Raman spectroscopy, the authors suggested that the structural phase transition in the temperature range near the MIT is suppressed by epitaxial strain, and the electronic transition triggers the MIT in strained films [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the application of VO 2 as a smart window material has three main challenges: a) lowering the T c to comfortable room temperature, b) increasing the visible light transmittance ( T lum ), and c) increasing the solar energy regulation ability (Δ T sol ). To obtain these aims, the researchers have tried many ways to regulate the performance of VO 2 , such as, doping with foreign elements, forming point defects, exerting external pressure, and designing of multi‐layer structures . Among these methods, the elemental doping is an effective way to change T c to comfortable room temperature by controlling the doping ratio.…”
Section: Introductionmentioning
confidence: 99%